Serological response of commercial dairy cattle to inactivated foot-and-mouth disease vaccine (type-O & A) in Nigeria - Lazarus, David Dazhia; Wungak, Yiltawe Simwal; Adah, Mohammed Ignatius; Ibu, John Okpapi; Abenga, Jerry Ngutor; Ekong, Pius Stephen; Ularamu, Hussaini Gulak (Asian Journal of Medical and Biological Research, 2015)
An observational study was conducted in a peri-urban dairy establishment in Jos South, Plateau State Nigeria to determine immune response of dairy cattle to commercial inactivated foot-and-mouth disease vaccine serotypes (O and A). Thirty seven Friesian cattle aged ?2years old with their crosses (15 selected pre-vaccination and 22 selected 21 days post-vaccination) were investigated for immune response to vaccination with an inactivated trivalent FMD vaccine containing serotypes O, A and SAT 2). Sera collected on day 0 pre-vaccination and 21 days post-vaccination was tested for structural protein antibodies to FMD serotypes O and A using the Solid Phase Competitive ELISA assay. The mean OD value for serum end point titre of FMD serotype O pre-vaccination was 11.64% with 6.67% (95%CI: 0.33 28.73) of the selected cattle being seropositive, at 21 days post-vaccination the mean OD value in selected cattle was 52.83% with 68.18% (95%CI: 46.95 84.89) of the selected cattle seropositive. For the FMD serotype A, 26.67% (95%CI: 9.10 52.53) of the selected cattle were seropositive pre-vaccination with a mean OD value of 29.21% and by 21 days post-vaccination, 72.73% (95%CI: 51.67 88.13) of the selected cattle were seropositive with a mean OD value of 61.70%. Serological response to vaccination improved in most selected cattle by 21 days post-vaccination. This study result has indicated that commercial inactivated FMD vaccines used for the prophylactic control of FMD in commercial dairy farm in Nigeria provoked immune response after a single shot. Asian J. Med. Biol. Res. June 2015, 1(2): 163-168